Bismuth intoxication resulting in acute kidney injury in a pregnant adolescent girl - Çelebi-Tayfur, Aslı; Yaradılmış, Raziye Merve; Ulus, Fatma; Çaltık-Yılmaz, Aysun; Özayar, Esra; Koşar, Berrin; Büyükkaragöz, Bahar; Horasanlı, Eyüp (The Turkish Journal of Pediatrics, 2019)
Bismuth intoxication is a rare cause of acute kidney injury (AKI) and is usually reversible by appropriate therapeutic measures. We present here a case of an adolescent pregnant girl who developed AKI due to an overdose of colloidal bismuth subcitrate (CBS, total amount of 6 g). She received parenteral chelating agent dimercaprol for 14 days. Continuous venovenous hemodiafiltration (CVVHD) with high-flux membrane was carried out in the first 3 days of chelating therapy and intermittent hemodialysis for 11 days, thereafter. The patient recovered clinically and was discharged after 21 days. She gave birth to a healthy term boy. At the last visit, the baby was 6 months old with normal growth and development as well as normal kidney functions. Neither deterioration in renal functions nor emergence of proteinuria was recorded in the patient during follow-up care after hospital discharge. In cases of AKI due to an overdose of CBS, treatment with dimercaprol combined with high flux hemodiafiltration and subsequently hemodialysis appears to be both useful and safe for bismuth elimination.
Keywords: acute kidney injury; bismuth intoxication; dimercaprol; teratogenicity